Molecular Imaging of the Kinetics of Vascular Endothelial Growth Factor Gene Expression in Ischemic Myocardium - Wu, Joseph C. (2004)
BACKGROUND: Angiogenic gene therapy is a promising treatment paradigm for patients with ischemic heart disease. In this study, we used micro–positron emission tomography (microPET) to monitor the transgene expression, function, and effects in a whole-body system. METHODS AND RESULTS: Adenovirus with cytomegalovirus promoter driving an angiogenic gene (vascular endothelial growth factor [VEGF]) linked to a PET reporter gene (herpes simplex virus type 1 mutant thymidine kinase; Ad-CMV-VEGF(121)-CMV-HSV1-sr39tk) was used to transfect rat embryonic cardiomyoblasts in vitro. Expression of both genes correlated strongly (r=0.98; P<0.001). Afterward, rats underwent ligation of the left anterior descending artery followed by injection of 1×10(10) pfu of Ad-CMV-VEGF(121)-CMV-HSV1-sr39tk (study; n=35) or Ad-null (control; n=15) at the peri-infarct region. Noninvasive microPET imaging was used to assess the uptake of 9-(4-[(18)F]-fluoro-hydroxymethylbutyl)guanine ([(18)F]-FHBG) PET reporter probe by cells expressing the HSV1-sr39tk PET reporter gene. Cardiac transgene expression peaked at day 1 and declined over the next 2 weeks. Repeat adenoviral injections at day 60 yielded no detectable signal. The in vivo reporter gene expression (% injected dose/g of [(18)F]-FHBG) correlated well with ex vivo gamma counting (r=0.92), myocardial tissue HSV1-sr39TK enzyme activity (r=0.95), and myocardial tissue VEGF level (r=0.94; P<0.001 for all). The VEGF(121) isoform induced significant increases in capillaries and small blood vessels. However, the level of neovasculature did not translate into significant improvements in functional parameters such as myocardial contractility by echocardiography, perfusion by nitrogen-13 ammonia imaging, and metabolism by [(18)F]-fluorodeoxyglucose imaging. CONCLUSIONS: Taken together, these findings establish the feasibility of molecular imaging for monitoring angiogenic gene expression with a PET reporter gene and probe noninvasively, quantitatively, and repetitively. The principles demonstrated here can be used to evaluate other therapeutic genes of interest in animal models before future clinical trials are initiated.